Systematic approach to bicontinuous cubic phases in ternary amphiphilic systems - Schwarz, Ulrich S.; Gompper, Gerhard (Physical review. E, Statistical, nonlinear, and soft matter physics, 1999)
The Fourier approach and theories of space groups and color symmetries are used to systematically generate and compare bicontinuous cubic structures in the framework of a Ginzburg-Landau model for ternary amphiphilic systems. Both single and double structures are investigated; they correspond to systems with one or two monolayers in a unit cell, respectively. We show how and why single structures can be made to approach triply periodic minimal surfaces very closely, and give improved nodal approximations for G, D, I-WP, and P surfaces. We demonstrate that the relative stability of the single structures can be calculated from the geometrical properties of their interfaces only. The single gyroid G turns out to be the most stable bicontinuous cubic phase since it has the smallest porosity. The representations are used to calculate distributions of the Gaussian curvature and 2H-nuclear-magnetic-resonance band shapes for C(P), C(D), S, C(Y), and F-RD surfaces.
Published online: 14 December 1998
Gesehen am 18.12.2017